Fabrication of Chiral‐Selective Nanotubular Heterojunctions through Living Supramolecular Polymerization. Issue 33 (29th June 2016) - Ma, Xiaojie; Zhang, Yibin; Zhang, Yifan; Liu, Yin; Che, Yanke; Zhao, Jincai
Abstract: Novel, chiral‐selective linear nanotubular heterojunctions were achieved by living supramolecular polymerization of perylenediimide (PDI) derivatives. We demonstrate that the chiral seed can effectively bias achiral PDI molecules to polymerize on its ends in the identical helical sense. More interestingly, the chiral seed can bias the opposite enantiomers to grow expitaxially from its ends even in excess amounts relative to the seed. Furthermore, we demonstrate that the biasing effect of the chiral seed on the opposite enantiomer is not dependent on the length of the chiral seed but is related to the intrinsic length of the elongated nanotube from the opposite enantiomer. The fabrication of chiral‐selective nanotubes was achieved by application of the unique biasing effect of the chiral seed in living supramolecular self‐assembly. Abstract : A perfect role model : Chiral‐selective linear nanotubule heterojunctions were achieved by living self‐assembly. Chiral perylenediimide (PDI)‐based nanotube seed ( S )‐1 not only induced the supramolecular polymerization of microribbons of an achiral PDI derivative2 at the seed ends in the same helical sense but could also polymerize the opposite enantiomer ( R )‐1 in the same helical sense; this biasing depended on the final tube length.